2017
DOI: 10.1021/acs.organomet.7b00846
|View full text |Cite
|
Sign up to set email alerts
|

Slurry-Phase Ethylene Polymerization Using Pentafluorophenyl- and Pentafluorophenoxy-Modified Solid Polymethylaluminoxanes

Abstract: Post synthesis modification of solid polymethylaluminoxane (sMAO) with tris(pentafluorophenyl)borane or pentafluorophenol produces highly active metallocene supports "sMMAOs" for use in slurry-phase ethylene polymerization. Characterization of the sMMAOs using ICP-MS analysis, BET isotherm, SEM-EDX, diffuse FT-IR and solid state NMR spectroscopy reveals that the surface methyl groups are exchanged for C 6 F 5 and C 6 F 5 O moieties respectively, giving a material with reduced aluminum content and a lower speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 82 publications
1
30
0
Order By: Relevance
“…[12][13][14] Observed activities are significantly higher than for other supports; for example sMAO-rac-ethylenebis(1-permethylindenyl)zirconium dichloride is at least three times more active than its silicasupported MAO counterpart (5365 vs. 1649 kg PE mol Zr À1 h À1 bar À1 respectively). 15,16 Furthermore, we have shown that reaction of sMAO with tris(pentafluorophenyl)borane or pentafluorophenol produces highly active modified-sMAO supports which show enhanced polymerisation activity with both rac-ethylenebis(1-indenyl) zirconium dichloride, rac-(EBI)ZrCl 2 , 17 and a range of unsymmetrical ansa-bridged permethylindenyl complexes. 18 Characterisation of sMAO using multinuclear NMR spectroscopy in solution and in the solid state reveals an aluminoxane structure that features ''structural'' and ''free'' AlMe x units in addition to benzoate residues.…”
Section: Introductionmentioning
confidence: 90%
“…[12][13][14] Observed activities are significantly higher than for other supports; for example sMAO-rac-ethylenebis(1-permethylindenyl)zirconium dichloride is at least three times more active than its silicasupported MAO counterpart (5365 vs. 1649 kg PE mol Zr À1 h À1 bar À1 respectively). 15,16 Furthermore, we have shown that reaction of sMAO with tris(pentafluorophenyl)borane or pentafluorophenol produces highly active modified-sMAO supports which show enhanced polymerisation activity with both rac-ethylenebis(1-indenyl) zirconium dichloride, rac-(EBI)ZrCl 2 , 17 and a range of unsymmetrical ansa-bridged permethylindenyl complexes. 18 Characterisation of sMAO using multinuclear NMR spectroscopy in solution and in the solid state reveals an aluminoxane structure that features ''structural'' and ''free'' AlMe x units in addition to benzoate residues.…”
Section: Introductionmentioning
confidence: 90%
“…This insoluble 'solid MAO' can act simultaneously as both co-catalyst and support in slurry phase ethylene polymerisation. 28,29 Results and discussion Synthesis of ( 3-R Ind # ) 2 ZrX 2 (R ¼ Me, Et or Ph; X¼ Cl, Br or CH 2 Ph)…”
Section: Introductionmentioning
confidence: 99%
“…27 This additive has proven useful in monitoring both aging and oxidation of MAO, 28,29 features known to be important in affecting the efficacy of this elusive but important activator. [30][31][32] We have also studied the reaction of MAO-activated Cp 2 ZrMe 2 with ethylene in toluene solution at low ethylene pressures. 33 In that case, a hitherto undetected, but long-suspected process for catalyst deactivation 34 was revealed by ESI-MS -formation of inactive, dinuclear Zr 2 complexes arising from the reaction of active species (i.e.…”
Section: Introductionmentioning
confidence: 99%